OPPORTUNITIES AND CHALLENGES OF WEAKER SECTIONS GIRL CHILDREN OF DELHI GOVT. AIDED SCHOOLS - Bhatia, Rajiv (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India is at a unique moment when social movements and civil society initiatives have culminated in several progressive legislations. With a strong Right to Education (RTE) mandate on quality education and teacher norms, the schools today are hit with trio of potent reforms in student evaluation, teacher evaluations and the most required and discussed teacher education reforms. Each of these reforms challenges the status quo, demanding that schools and teacher education institutions systematically and continuously improve student and teacher performance, marking and measuring their progress at each and every step along the way. What they however fail to focus at is that learning is collective rather than an individual activity and teaching is a social practice than only a technical skill highlighting the closeness in the education and society relationship. This entails significant change in the way teachers and teacher educators are defined, understood and therefore nurtured. This is not just about providing professional development but about nurturing a genre of teachers who are passionately engaged in the pursuit of reflecting and learning and through their efforts create kind of environment in schools that develop responsible citizens, life-long learners, economically and socially industrious individuals, and compassionate human-beings. Going by the term Economically Weaker Sections (EWS) it is used to refers to those citizen or household with income below a certain threshold level. Though may be other economic factors in deciding on the economic weakness of citizen/household, income is the dominant criterion. In public policy domain the term has to be appreciated in the context of the preamble to India’s Constitution which seeks Justice, Social, Economic and Political.